2017
DOI: 10.1186/s12891-017-1798-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bone morphology on the outcome of the pivot shift test: a cohort study

Abstract: BackgroundThe presence of a positive pivot shift after surgical repair of the ACL is considered an important indicator of a failed reconstruction. The ability to predict the result of a pivot shift test after an ACL reconstruction using variables that can be measured prior to surgery could provide an indication of which patients may be at-risk of a poor surgical outcome.The purpose of this study was to determine whether structural characteristics of the femur and tibia, measured using plain radiographs, were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…15 The lateral femoral condylar to tibia size ratio is usually above 1.42 and more evident in some knees especially females. 8 Femoral movement over the tibia in early flexion consists of rolling and gliding at a ratio of 1:2. This progresses to a 1:4 ratio during later flexion.…”
Section: Anatomymentioning
confidence: 99%
See 2 more Smart Citations
“…15 The lateral femoral condylar to tibia size ratio is usually above 1.42 and more evident in some knees especially females. 8 Femoral movement over the tibia in early flexion consists of rolling and gliding at a ratio of 1:2. This progresses to a 1:4 ratio during later flexion.…”
Section: Anatomymentioning
confidence: 99%
“…7 The tibial eminence with its twin spines acts as a boney barrier to excessive tibial rotation and translation. 8 Increasing rotational torque will force the femur to ascend the tibial eminence thus producing distraction forces which are strongly opposed by the collateral ligaments, tendons, and capsule. 9 Named for their tibial origins, the ACL has two recognized bundles oriented at 40°to the long axis of the femur.…”
Section: Anatomymentioning
confidence: 99%
See 1 more Smart Citation
“…Branch et al examined a group of patients who had undergone ACL reconstruction and evaluated their bony morphology radiographically. A significantly higher rate of post-operative pivot shift was observed when patients had a higher femur-tibia size ratio (FRSR), when the femur was larger relative to the tibia, or a smaller tibia to posterior femoral condyle ratio (TPFCR), and when there was smaller tibial depth relative to the depth of the lateral posterior condyle [51].…”
Section: Bony Morphologymentioning
confidence: 99%
“…Among the anatomical factors, the influence of the anatomic variance of the lateral compartment has recently attracted considerable research interest [5]. Some studies have shown that the spherical shape of the lateral femoral condyle has a clear relationship with the relative axial movement of tibiofemoral joint and the ACL rupture [6,7]. The purpose of this study was to describe the distal curvature of the lateral femoral condyle use ratio of height of lateral femoral condyle to anteroposterior diameter (HAPR), and to evaluate its correlation with ACL rupture.…”
Section: Introductionmentioning
confidence: 99%